The Rise of Banditry in Northwest Nigeria: Examining the Security Implications and Pathways to Stability - Rufus, Anthony Israel; Ogbe, Ekoja Bernard (Kashere Journal of Politics and International Relations, 2024)
The rise of banditry in Northwest Nigeria has emerged as a significant threat to regional security, posing severe challenges to governance, public safety, and socio-economic stability. This paper examines the root causes of banditry in the region, including widespread poverty, unemployment, and competition over scarce resources, particularly in rural areas. The weakening of state authority and poor law enforcement have further exacerbated the problem, allowing armed groups to operate with impunity. The security implications are profound, ranging from violent attacks on villages and kidnappings for ransom to the displacement of thousands of people, creating a humanitarian crisis. This paper also explores the intersection of banditry with other forms of criminality, such as cattle rustling, arms smuggling, and links to terrorist groups, complicating efforts to restore order. As banditry spreads across the region, it undermines public trust in government institutions, hampers economic development, and fosters political instability. In response to the challenges, this paper evaluates various pathways to stability, including strengthening local governance, improving law enforcement capabilities, and addressing the underlying socio-economic drivers of crime. Cross-border cooperation between Nigeria and neigbouring states is also considered essential, given the transnational nature of bandit operations. The paper advocates for holistic approach, combining security measures with long-term investments in education, healthcare, and infrastructure to address the root causes of violence. Ultimately, the study argues that a comprehensive, multi-sectoral strategy is key to mitigating the threat of banditry and restoring peace and security in Northwest Nigeria.